Invitation To The VR Forest: Gen Z And Sustainability Learning - Andziak, Anita (Global journal of Business and Integral Security, 2026)
This study evaluates EcoVerse a virtual reality (VR) “VR Forest” module combining immersive storytelling, gamification, and environmental education as a catalyst of Gen Z environmental learning. In a quasi-experimental pre-test/post-test design (N = 89; 18–26 years), a control group completed a traditional forest tour, while the experimental group experienced VR + tour. Compared to control, the hybrid condition showed larger gains in environmental knowledge (ΔM = 2.5 vs 1.2 points), positive affect on PANAS (ΔM = 1.6 vs 0.8), pro-environmental intentions (ΔM = 1.9 vs 0.9), and NEP attitudes (ΔM = 1.5 vs 0.7). Between-group differences were statistically significant (t-tests; ANOVA interaction). Qualitative data indicated stronger symbolic and cultural associations with forests after VR. Findings position VR as a complementary tool in sustainable tourism and environmental education for Gen Z, enhancing knowledge, affect, and pro-environmental orientations.